Modern Changes of the Climatic Conditions andRhythmicity of the Long-Term Oscillations of theMode Parameters of Water Bodies as the IntegralIndex of the Climate Fluctuation(based on the Urals example); Advances in Systems Science and Application (ASSA); Vol.15, iss. 3 - Rasskazova N. S. Nadezhda Stepanovna; Bobylev A. V. Aleksandr Vladimirovich; Bubin M. N. Mikhail Nikolaevich; Malaev A. V. Aleksandr Vladimirovich (2015, 2015)
Title screen